1551. Cat Scratch Disease as a Mimicker of Malignancy: Rare and Elusive. (31st December 2020) - Dhal, Udit; Tarrand, Jeffery; Kontoyiannis, Dimitrios P
Abstract: Background: Cat scratch disease (CSD) mimicking malignancy has been the subject of scattered case reports. To that end, we reviewed patients (pts) with CSD at MD Anderson Cancer Center (MDACC), focusing on the clinical overlap of CSD presentation with that of malignancy. Methods: We retrospectively reviewed all pts diagnosed with CSD at MDACC (11/2015-1/2020). CSD was diagnosed based on Bartonella henselae serology, animal exposure and biopsy findings consistent with the diagnosis. We collected data on CSD epidemiology, signs, symptoms, laboratory findings, histopathology, radiological studies, treatment used, outcome and the malignancy mimicked. We also reviewed the published cases of CSD mimicking malignancy (1952-2020). Results: We identified 11 such pts; 1 (9%) was male and 5(45%) were ≤ 18 years old. No pt had a prior history of malignancy. All but 1 pt reported an exposure to cats. Only 2/11 (18%) had fever, and none of the pts had skin lesions or hepatosplenomegaly. All pts had lymphadenopathy; 2/11 (18%) had only inguinal lymphadenopathy. PET scan was performed for 3 pts and revealed only enlarged lymph nodes. Several malignancies were considered as initial diagnostic impressions, including sarcoma (n=3), lymphoma (n=2), breast cancer (n=2). Serum Bartonella IgG titer was ≥ 1:512 in 9/11(82%) pts with 3 pts (28%) positive for IgM. 8 pts had a biopsy and non-necrotizing granuloma was the most common finding, present in 4. Azithromycin was used in all 8 pts that were treated. Nearly all pts improved or had resolution of symptoms with one pt having persistent fever and lymphadenopathy. Literature search identified 33 cases of CSD that mimicked malignancy (10 for breast cancer, 10 for lymphoma, 6 for sarcoma with 1 each for lung, pancreatic, parotid and 4 others). Conclusion: Although there was a probable referral bias in the CSD pts at MDACC, CSD should be included in the differential diagnosis of malignancy. Although publication biases are probable, literature review also supports the notion that atypical CSD rarely can simulate a variety of malignancies. Disclosures: Dimitrios P. Kontoyiannis, MD, Amplyx Pharmaceuticals (Consultant)Astellas Pharma (Consultant)Ciadara Therapeutics (Consultant)Gilead Sciences (Other Financial or Material Support, Honoraria)Mayne Pharma (Consultant)Merck & Co (Consultant, Honoraria)Pharma (Consultant)United Medical (Other Financial or Material Support, Honoraria)